History of Preeclampsia Adds to the Deleterious Effect of Chronic Stress on the Cardiac Ability to Flexibly Adapt to Challenge - Lackner, Helmut K.; Moertl, Manfred G.; Schmid-Zalaudek, Karin; Lucovnik, Miha; Weiss, Elisabeth M.; Kolovetsiou-Kreiner, Vassiliki; Papousek, Ilona (Frontiers in Physiology, 2018)
Preeclampsia, a pregnancy-specific disorder, presents a major health problem during gestation, but is also associated with increased risk for cardiovascular complications in later life. We aimed to investigate whether chronic stress experience and preeclampsia may have additive adverse effects on the cardiac ability to flexibly adapt to challenge, that is, to mount an appropriately vigorous heart rate response to an acute psychological challenge, or whether they may perhaps have synergistic effects (e.g., mutual augmentation of effects). Blunted cardiac responding to challenge has been linked to poor health outcomes in the longer term. Women previously affected by preeclampsia and women after uncomplicated pregnancies were tested 15–17 weeks post-partum in a standardized stress-reactivity protocol, while cardiovascular variables were simultaneously recorded. Changes in heart rate and blood pressure in response to the stressor were analyzed with regard to the effects of history of preeclampsia and chronic stress experience. Findings indicated blunted cardiac responses in women with higher chronic stress experience (p = 0.020) and, independently from that, in women with a history of preeclampsia (p = 0.018), pointing to an additive nature of the effects of preeclampsia and chronic stress on impaired cardiovascular functioning. Consequently, if both are present, a history of preeclampsia may add to the already deleterious effects of the experience of chronic stress. The additive nature of the effects suggests that stress-reducing interventions, albeit they will not eliminate the heightened cardiovascular risk in patients with a history of preeclampsia, may improve their overall prognosis by avoiding further accumulation of risk.